From Burst to Sustained Release: The Effect of Antibiotic Structure Incorporated into Chitosan-Based Films - Nathália F. Sczesny; Helton J. Wiggers; Cecilia Z. Bueno; Pascale Chevallier; Francesco Copes; Diego Mantovani (MDPI AG, 2024)
Background/Objectives: Medical devices are susceptible to bacterial colonization and biofilm formation, which can result in severe infections, leading to prolonged hospital stays and increased burden on society. Antibacterial films have the potential to assist in preventing biofilm formation, thereby reducing administration of antibiotics and the emergence of antibiotic-resistant strains. In a previous study, a chitosan-based matrix crosslinked with tannic acid and loaded with gentamicin was reported. In this study, five different antibiotics (moxifloxacin, ciprofloxacin, trimethoprim, sulfamethoxazole or linezolid) were loaded into these chitosan-based films, and their impact on the release behavior carefully assessed. Methods: The samples were characterized according to their thickness, swelling, and mass loss in phosphate-buffered saline (PBS), as well as by morphology using scanning electron microscopy (SEM) and optical phase contrast microscopy. Antibiotic release over time was quantified in PBS by high-performance liquid chromatography (HPLC). Antibacterial activity was investigated by disk diffusion test and antibiotic release over time. Finally, the cytotoxicity of the samples was assessed with human dermal fibroblasts. Results: The obtained results differed significantly, especially regarding the antibiotic release time and antibacterial activity, which varied from one day to six months, enabling classification of the films from burst/transient to prolonged release. The films also showed antibacterial features against bacteria mostly present in medical devices and displayed to be non-cytotoxic. Conclusions: In conclusion, it was demonstrated that the antibiotics structure significantly alters the release kinetics, and that by carefully selecting the antibiotic, the consequent release can be tuned. This approach yielded films that could be used for potentially-scalable release in antimicrobial coatings specific to medical devices, aiming to reduce biomaterial associated infections (BAIs).